Sensory Attenuation for Jointly Produced Action Effects - Loehr, Janeen D. (Frontiers in Psychology, 2013)
Successful joint action often requires people to distinguish between their own and others’ contributions to a shared goal. One mechanism that is thought to underlie a self-other distinction is sensory attenuation, whereby the sensory consequences of one’s own actions are reduced compared to other sensory events. Previous research has shown that the auditory N1 event-related potential (ERP) response is reduced for self-generated compared to externally-generated tones. The current study examined whether attenuation also occurs for jointly-generated tones, which require two people to coordinate their actions to produce a single tone. ERP responses were measured when participants generated tones alone (tone onset immediately followed the participant’s button press) or with a partner (tone onset immediately followed the participant’s or the partner’s button press, whichever occurred second). N1 attenuation was smaller for jointly-generated tones compared to self-generated tones. For jointly-generated tones, greater delays between the participant’s and the partner’s button presses were associated with reduced attenuation; moreover, only trials in which there was no delay between the participant’s press and tone onset showed attenuation, whereas trials in which there were delays did not show attenuation. These findings indicate that people differentiate between their own and another person’s contributions to a joint action at the sensorimotor level, even when they must act together to produce a single, shared effect.